Trends of adult admissions in a district hospital in Limpopo Province - Lourens, Adriaan Eksteen (My University, 2011)
BACKGROUND: District hospitals play an intermediary role between primary health care (PHC) clinics and community health centres; (CHC), (predominantly run by nurses) and regional hospitals, (predominantly run by specialists and doctors). However, in the absence of efficient and adequate network of PHC clinics and CHC’s, district hospitals often have to render these services. In addition, due to geographic distances between district hospitals and regional hospitals, it often has to offer specialist services such as Orthopaedics, Gynaecology, as well. This increases the burden on district hospitals. The profile of patients admitted to district hospitals have not been clearly described and this study seeks to describe and to compare trends over a two year period and factors influencing these trends, to allow for informed decisions to be made for future planning. No formal study on the trends for admissions to District hospitals have been conducted, as far as could be determined, and this study aimed to look into and describe the trends of admissions over a two year period from April 2007 to March 2009, to allow for informed decisions to be made to guide future plans. AIM: To determine the trends of adult admissions in a district hospital in Limpopo Province. METHODOLOGY: A cross-sectional study design was used for this study. A descriptive retrospective review of existing hospital records was conducted from routine information captured on the MEDICOM patient administration system and in ward and OPD/casualty registers. No intervention was done for this study. The setting was F. H. Odendaal Hospital in Modimolle, which is a district hospital situated in a rural area of the Limpopo Province. It serves a catchments population of over 103 000 people. Data was collected from 4481 admitted adult patients from which a random sample (n=800) was selected consisting of males (n=400) and females (n=400). Data on variables such as the case load (number of adult admissions during the research period), patient profile (gender, age, hospital classification and geographic location) and clinical profile (mode of admission, agnoses and associated ICD-10 code/s as well as the mode of discharge) were collected. RESULTS: This study revealed that this hospital experienced an increase number of adult admissions during the two years study period. During the same period it could reduce the length of stay, thereby improve usable bed utilisation rate. This reflected in more discharges and less death. This was probably due to availability of more experienced medical officers and the fact that outreach services has been conducted on a weekly basis by doctors and Clinical Support Services since 2008/09 financial year. The majority of the patients who were admitted over the study period were Africans residing in and around Modimolle. The majority was also classified as H1, meaning that most of the patients admitted to this hospital are capable of paying the nominal fee for services. The institution experienced an increase in the number of admission over the two years by 11.7%. The mean age was 42.5 years for adults. Of the top 5 diseases/conditions for which patients were admitted, Pneumonia, Diarrhoea and Gastroenteritis, Retrovirus infections and Diabetes Mellitus were present for both males and females. Although this disease pattern persists for a number of years, it seems as if services provided manage to reverse discharge trends as more patients were discharged home in the second year than in the first year and the mortality rate decreased by 4.5% for adults between the two years. CONCLUSION: Information obtained through this research could be extrapolated to other district hospitals for the management of services, including the management of beds. It could also serve as the basis for future research, as a reference base to students and the teaching of students.
Keywords: Admitting Department, Hospital